2017
DOI: 10.1515/aoter-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

System effects of primary energy reduction connected with operation of the CHP plants

Abstract: The paper is devoted to explication of one of the advantages of heat and electricity cogeneration, rarely considered in technical literature. Usually attention is paid to the fact that heat losses of the heat distribution network are less severe in the case of cogeneration of heat in comparison with its separate production. But this conclusion is also true in other cases when the internal consumption of heat is significant. In this paper it has been proved in the case of two examples concerning trigeneration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The calculated amounts of chemical energy saved in the fuel, in the case of cogeneration, are confirmed by the tests carried out on real facilities up to 0.5 MW, as well as on those with a greater capacity, the latter being municipal combined heat and power plants. Energy balance sheets for CHP systems have shown that the fuel energy savings ratio in the separate heat and power generation process is the appropriate measure of energy efficiency in the case of cogeneration [Ziębik and Gładysz, 2017].…”
Section: Energy Ratiosmentioning
confidence: 99%
“…The calculated amounts of chemical energy saved in the fuel, in the case of cogeneration, are confirmed by the tests carried out on real facilities up to 0.5 MW, as well as on those with a greater capacity, the latter being municipal combined heat and power plants. Energy balance sheets for CHP systems have shown that the fuel energy savings ratio in the separate heat and power generation process is the appropriate measure of energy efficiency in the case of cogeneration [Ziębik and Gładysz, 2017].…”
Section: Energy Ratiosmentioning
confidence: 99%
“…Cost-effective methods of energy management are important and ways to improve energy efficiency of thermal processes are crucial in industrial and commercial applications [1]. Some ways of using waste heat sources are known, such as absorption and adsorption technologies [2,3].…”
Section: Introductionmentioning
confidence: 99%